Copy Number Variants in Epileptic Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
An international group of investigators at University of Washington, Seattle, USA, and various centers in Australia, New Zealand, Canada, and Israel evaluated 315 patients with epileptic encephalopathies for rare copy number variants (CNVs) using a whole-genome oligonucleotide array.